2020
DOI: 10.1016/j.xinn.2020.100035
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming Resistance to Drugs Targeting KRAS Mutation

Abstract: Activating KRAS mutations are present in 25% of human cancer. Although oncogenic Ras was deemed “undruggable” in the past, recent efforts led to the development of pharmacological inhibitors targeting the KRAS G12C mutant, which have shown promise in early clinical trials. The development of allele-specific K-Ras G12C inhibitors marked a new chapter in targeting oncogenic KRAS mutant in cancer. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 104 publications
(312 reference statements)
1
54
0
Order By: Relevance
“…In conclusion, KRAS G12C specific inhibitors are a testament to the progress that has been made in targeting an oncogene that was previously considered “undruggable”. Two KRAS G12C inhibitors, adagrasib and sotorasib, have shown efficacy in early clinical trials and further clinical studies are underway [ 27 , 40 ]. Like the downstream targeted therapies that have preceded them, it is clear that G12C inhibitors will induce acquired resistance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In conclusion, KRAS G12C specific inhibitors are a testament to the progress that has been made in targeting an oncogene that was previously considered “undruggable”. Two KRAS G12C inhibitors, adagrasib and sotorasib, have shown efficacy in early clinical trials and further clinical studies are underway [ 27 , 40 ]. Like the downstream targeted therapies that have preceded them, it is clear that G12C inhibitors will induce acquired resistance.…”
Section: Resultsmentioning
confidence: 99%
“…A lack of dependency on KRAS signalling could account for some of the intrinsic resistance noted in pre-clinical models, which may underlie the variable response seen in patients [ 27 , 39 , 40 ]. RAS proteins exert their effects through multiple pathways, including the MAPK/ERK and PI3K/AKT/mTORC1 pathways, although the PI3K pathway is not dependent on RAS alone for activation [ 41 ].…”
Section: Mechanisms Of Resistance To Kras G12cmentioning
confidence: 99%
“…As for tumor invasion and metastasis, carcinoma-associated fibroblasts are able to enhance tumor cells migration and invasion via activating the process of specific pathways. For example, as lung cancer maintains the leading cause of cancer-related deaths, IPF has been demonstrated that it increases the risk of lung cancer development by 7–20%, and there are multiple common molecular processes that associated IPF with lung cancer, such as epithelial–mesenchymal transition (EMT), endoplasmic reticulum stress, and abnormal expression of growth factors ( Gu et al, 2018 , 2020a , b ; Ballester et al, 2019 ; Jiao and Yang, 2020 ). In the tissue of myopathies, there is prominent endomysial fibrosis, but little or no inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some specific compounds drugging wild type and oncogenic RAS or selectively drugging only specific mutant KRAS have been discovered and entered in clinical trials testing their efficacy on KRAS direct inhibition [ 17 , 18 , 19 , 20 ]. Nevertheless, these specific approaches also cause drug resistance, making necessary the identification of other strategies to avoid cancer cell adaptation [ 21 , 22 , 23 ]. Therefore, combined treatments able either to enhance the effects of the RAS inhibitors or to avoid the mechanisms of resistance are still needed [ 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, these specific approaches also cause drug resistance, making necessary the identification of other strategies to avoid cancer cell adaptation [ 21 , 22 , 23 ]. Therefore, combined treatments able either to enhance the effects of the RAS inhibitors or to avoid the mechanisms of resistance are still needed [ 21 , 24 ]. Indeed, new combined treatments, targeting cell cycle-related pathways, DNA repair related pathways, and metabolic pathways have already been proposed and are currently being tested in preclinical and clinical trials [ 21 ].…”
Section: Introductionmentioning
confidence: 99%